Managers perceptions about knowledge management and Organisational Wisdom - Rocha, Raysa (2020)
Accumulating knowledge does not guarantee better problem solving; thus, success is not about knowing more. The lack of success of Knowledge Management in generating the expected value and competitive advantages opened doors to Organisational Wisdom. Wisdom can be defined as the capacity to put into action the most suitable behaviour, considering what is known and what does the most good. The purpose of this article is to understand the perception of managers about Knowledge Management and Organisational Wisdom. The research conducted was exploratory on a qualitative method. The interviews were developed electronically in organisations located in Brazil, Portugal, Bulgaria, Serbia, Angola, Argentina, Australia, and China. There is a disparity between the advancement of theory and practice in organisations. It concludes that managers have a simplistic notion of what Knowledge Management is, they do not understand the idea of "ba" and are focused on explicit knowledge, they still fail to understand in a global way knowledge and how it should be managed and have almost no notion of what organisational wisdom is. They understand the importance of the leader, mainly because they are leaders, giving importance to their function.